Silicene-based layered materials : essential properties /: essential properties. ([2020]) - Lin, Shih-Yang; Liu, Hsin-Yi; Nguyen, Duy Khanh; Tran, Ngoc Thanh Thuy; Pham, Hai Duong; Chang, Shen-Lin, 1963-; Lin, Chiun-Yan; Lin, Ming-Fa
No abstract available